Letrozole-Assisted Ovulation Induction Combined with Lifestyle Modification in Women with PCOS: A Review - Waśniowska, Magdalena; Wiernek, Magdalena; Węgrzyn, Jagoda (Journal of Education, Health and Sport, 2026)
Introduction. Polycystic ovary syndrome (PCOS) is a leading cause of anovulatory infertility. Lifestyle modification remains the foundation of treatment, yet many women require pharmacological ovulation induction. Letrozole, an aromatase inhibitor originally developed for breast cancer therapy, has emerged as a promising first-line agent for women with PCOS. Aim. The aim of this article is to assess whether it is clinically appropriate to use letrozole in addition to physical activity and nutrition to achieve better ovulation outcomes in women with PCOS trying to improve infertility. Review methods. A thorough examination of research articles on PubMed and Google Scholar was conducted using search phrases that included the following keywords: letrozole/ off-label use/ ovulation induction/ female infertility/ polycystic ovary syndrome/ aromatase inhibitors/ diet/ lifestyle modification/ stimulated cyclear.